Prevalence, Risk Factors and Short-term Outcomes of Acute Kidney Injury in Women with Obstetric Complications in Dar Es Salaam, Tanzania (Tanzania Medical Journal, 2022)
IntroductionPregnancy-related acute kidney injury (PRAKI) is still reported in developing countries contributing to both maternal and fetal morbidity and mortality. In this study, we report on the burden, risk factors and outcomes of PRAKI among pregnant women with obstetric complications at Muhimbili National Hospital (MNH), Dar es Salaam, Tanzania.MethodologyThis was a hospital-based descriptive cross-sectional study involving women with obstetric complications in late pregnancy, admitted into obstetric wards at MNH, Dar es Salaam, Tanzania. Acute Kidney Injury Network (AKIN) criterion was used to define acute kidney injury (AKI). Data analysis was done using the Statistical Package of Social Sciences (SPSS) version 23.ResultsDuring the study period a total of 5448 deliveries occurred at Muhimbili National Hospital (MNH) amongst whom 1150 (21.1%) women had obstetric complications. AKI occurred in 99(8.6%) categorized into AKIN stage I (55.5%), II (8.1%), and III (36.4%). Hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome and severe pre-eclampsia were the most frequent obstetric complications among patients with PRAKI. On further analysis, PRAKI was associated with advanced maternal age, being HIV positive, having history of hypertension and/or having elevated blood pressure, albuminuria and having anemia detected during antenatal clinic (ANC) visits. Hemodialysis was offered to 6.1% (6/99) of the patients with PRAKI. Among patients with PRAKI, 27 (27.3%) had complete recovery of renal function at the time of discharge. On considering fetal outcome; PRAKI was associated with delivering a stillbirth baby.ConclusionPRAKI is common among women with obstetric complications and its risk factors include advanced maternal age, being HIV positive, having history of hypertension and/or having elevated blood pressure, albuminuria or anemia detected during antenatal clinic visits. Early recognition and treatment of PRAKI may help prevent associated poor maternal and fetal outcomes.